MMPI-2 Domain and Psychological Distress in Clinical Medical Students - Kusumastiwi, Tesaviani; Arifrizqi, Muhammad; Susanti, Eska; Puspitosari, Warih (HM Publisher, 2023)
Introduction: The clinical rotation is a stage of medical education that provides a stressful environment for medical students. Psychological distress in medical students affects the learning output and achievement of clinical competencies. MMPI-2 is a screening tool for mental disorders in clinical medical student admission protocols. Nevertheless, the domain for predicting psychological distress during clinical rotation has not been considered before. The aim of the study is to determine the MMPI-2 domain as a predictor of future psychological distress in clinical rotation students. Methods: This study used a cross-sectional and retrospective design using the MMPI-2 data derived from admission protocols and the SRQ (self-reporting questionnaire-29) questionnaire measuring the psychological distress in first-year clinical rotation students. Results: 87 data showed that not all MMPI-2 domains were statistically associated with psychological distress in clinical medical students. Domains of psychasthenia (Pt), psychopathic deviated (Pd), neurotic personality (NEGE), introverted personality (Intr), and lower stress resistance (ES) were the best predictors of psychological distress during the clinical process. Conclusion: The psychological distress of clinical medical students can be predicted by Pd, Pt, Nege, Intr, and Es scores of MMPI-2 with cut-off points 40T and 50T.